JOB STRESS AMONG CIVIL SERVANTS: THE ROLE OF WORKLOAD AND WORK ENVIRONMENT - Herdiana, Fauzia; Purwana, Dedi; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
Excessive work stress can cause a decline in mental and physical health, decreased productivity, and increased levels of employee absenteeism and turnover. The purpose of this study is to investigate the impact of workload and work environment on employees' work-related stress. The research employed a quantitative method and collected primary data through questionnaires distributed using proportional random sampling techniques. The population consisted of 160 employees, and the sample size was determined to be 110 employees based on the Isaac and Michael table formula with a 5% margin of error. The data was processed using SPSS version 29.0 by conducting multiple regression analysis. The findings of this research indicate that both workload and work environment have a positive and significant impact on work-related stress, whether examined separately or together. This research provides insight into how workload and work environment influence stress among employees, which can help design more effective policies and interventions to improve their well-being and productivity.